Dynamic compression enhances pressure-to-pain threshold in elite athlete recovery: exploratory study - Sands, W. A.; McNeal, J. R.; Murray, S. R.; Stone, M. H. (The Journal of Strength and Conditioning Research, 2015)
Athlete recovery-adaptation is crucial to the progress and performance of highly trained athletes. The purpose of this study was to assess peristaltic pulse dynamic compression (PPDC) in reducing short-term pressure-to-pain threshold (PPT) among Olympic Training Center athletes after morning training. Muscular tenderness and stiffness are common symptoms of fatigue and exercise-induced muscle microtrauma and edema. Twenty-four highly trained athletes (men = 12 and women = 12) volunteered to participate in this study. The athletes were randomly assigned to experimental (n = 12) and control (n = 12) groups. Pressure-to-pain threshold measurements were conducted with a manual algometer on 3 lower extremity muscles. Experimental group athletes underwent PPDC on both legs through computer-controlled circumferential inflated leggings that used a peristaltic-like pressure pattern from feet to groin. Pressures in each cell were set to factory defaults. Treatment time was 15 minutes. The control group performed the same procedures except that the inflation pump to the leggings was off. The experimental timeline included a morning training session, followed by a PPT pretest, treatment application (PPDC or control), an immediate post-test (PPT), and a delayed post-test (PPT) after the afternoon practice session. Difference score results showed that the experimental group's PPT threshold improved after PPDC treatment immediately and persisted the remainder of the day after afternoon practice. The control group showed no statistical change. We conclude that PPDC is a promising means of accelerating and enhancing recovery after the normal aggressive training that occurs in Olympic and aspiring Olympic athletes.